Impact of Fii in recent stock market volatility / D. S. Selvakumar - D. S., Selvakumar (2010)
The growth of relationship of interdependence between individuals and institutions across geographical and political boundaries through globalisation leads to increase of flow of investments capital. Globalisation refers to a process of increasing economic integration and growing economic interdependence between countries in the world economy. For a developing country, opening up of the stock market to FII can act as catalyst in improving efficiency of the market. As FII arrival is associated with the importation of sophisticated financial technology, adoption of the technology to the domestic environment, and greater investments in improving information processing and financial services. However these benefits should be weighted against uncertainties associated with opening up of the market. One of the major concerns is that the portfolio funds may lead to greater volatility in domestic stock prices. If foreign stock prices for any reason fluctuate the domestic prices will also respond to the fluctuations. This paper focuses on the impact of FIIs in the stock market volatility in recent times.